ISLAMIC FAMILY MEDIATION IN SOUTHEAST ASIA: AN ANALYSIS OF CULTURAL LEGITIMACY, LEGAL STRUCTURE, AND CONTEMPORARY DYNAMICS IN INDONESIA AND MALAYSIA - Rahma Khofifah Khoirun Umah; Nur Fadhilah; M. Darin Arif Mu'allifin (Universitas Islam Indonesia, 2025)
Purpose – This study examines the legal framework and institutional practices of family dispute mediation in Indonesia and Malaysia within the context of Islamic family law. This study aims to evaluate how legal pluralism, religious values, and cultural norms shape the implementation and effectiveness of mediation mechanisms in both countries by comparing the effectiveness of the regulation and implementation of family mediation in Indonesia and Malaysia, highlighting Indonesia's reliance on mediation and Malaysia's reliance on the Majlis Sulh. Methods – This study employs a qualitative legal methodology with doctrinal, comparative, and empirical approaches. The regulations compared include PERMA No. 1 of 2016 and related regulations in Indonesia, as well as the Islamic Family Law Act 1984 (Act 303) and Kaedah-Kaedah Sulh in Malaysia. The analysis examines the legal framework, institutions, and implementation of family mediation, supported by institutional data from the Supreme Court of the Republic of Indonesia (2022) and the Malaysian Sharia Judicial Department (2020). Findings – The findings reveal significant contrasts: while Indonesia relies heavily on court-annexed mediation led by judges, Malaysia has institutionalized Sulh through the Syariah Court's Majlis Sulh, featuring trained officers and standardized procedures. In Indonesia, mandatory mediation often lacks adequate screening for domestic violence, which raises ethical concerns. Conversely, Malaysia's structured system demonstrates greater procedural integrity and role clarity. Cultural and psychosocial dimensions further influence the outcomes. Community-based models in Indonesia emphasize negotiated resolutions, whereas Malaysia prioritizes religious legitimacy and professionalization. The role of psychosocial professionals and child-inclusive practices emerged as vital elements for increasing effectiveness. Legal culture, public trust, and the institutional environment also determine how mediation is perceived and practiced, with Malaysia benefiting from clearer legal demarcation. Research contribution/limitations – This study contributes to the growing body of literature on Islamic legal pluralism and non-adversarial justice by identifying the institutional, cultural, and ethical factors that enhance or constrain mediation in Muslim-majority contexts.